Islam dan Ahl al-Kitab - Umi Sumbulah (IAIN Ponorogo, 2011)
This study aims at understanding the perception of Nahdlatul Ulama (NU), Muhammadiyah and Hizb al-Tahrir leaders in Malang, East Jawa, about the relation of Islam with Ahl al-Kitāb, includes their implications toward social life. The result shows that there are varied concepts on the meaning of Ahl al-Kitāb. According to NU and Muhammadiyah, Ahl al-Kitāb are Jewish and Christian community who still or not recognize the oneness of Allah. Conversely, Hizbut Tahrir state that the term refers merely to Jewish and Christian who embrace the “genuine” theological system. In understanding the hadis, the three organizations are polarized into three models; combining pure Islamic sciences with modern sciences as performed by the NU’s followers (Nahdhiyin); applying contextual approach and modern sciences as used by Muhammadiyah; and focusing on text as Hizbut Tharir choose. However, although the three organizations have different understanding on the concept of Ahlal-Kitab, they they have no objection to establish social relationship with them.